Cluster Analysis to Identify Possible Subgroups in Tinnitus Patients - van den Berge, Minke J. C.; Free, Rolien H.; Arnold, Rosemarie; de Kleine, Emile; Hofman, Rutger; van Dijk, J. Marc C.; van Dijk, Pim (Frontiers in Neurology, 2017)
Introduction. In tinnitus treatment, there is a tendency to shift from a ‘one size fits all’ to a more individual, patient-tailored approach. Insight in the heterogeneity of the tinnitus spectrum might improve the management of tinnitus patients in terms of choice of treatment and identification of patients with severe mental distress. The goal of this study was to identify subgroups in a large group of tinnitus patients. Methods. Data was collected from patients with severe tinnitus complaints visiting our tertiary referral tinnitus care group at the University Medical Center Groningen. Patient reported and physician reported variables were collected during their visit to our clinic. Cluster analyses were used to characterize subgroups. For the selection of the right variables to enter in the cluster analysis, two approaches were used: (1) variables reduction with Principle Component Analysis and (2) variable selection based on expert opinion. Results: Various variables of 1783 tinnitus patients were included in the analyses. Cluster analysis (1) included 976 patients and resulted in a four-cluster solution. The effect of external influences was the most discriminative between the groups, or clusters, of patients. The ‘silhouette measure’ of the cluster outcome was low (0.2), indicating a ‘no substantial’ cluster structure. Cluster analysis (2) included 761 patients and resulted in a three-cluster solution, comparable to the first analysis. Again, a ‘no substantial’ cluster structure was found (0.2). Conclusion. Two cluster analyses on a large database of tinnitus patients revealed that clusters of patients are mostly formed by a different response on external influences on their tinnitus. However, both cluster outcomes based on this dataset showed a poor stability, suggesting that our tinnitus population comprises a continuum rather than a number clearly defined subgroups.